-23+5(7-12x)=7(1-6x)-3(2x+1)

Simple and best practice solution for -23+5(7-12x)=7(1-6x)-3(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23+5(7-12x)=7(1-6x)-3(2x+1) equation:


-23+5 (7-12x)=7 (1-6x)-3 (2x+1)

We simplify the equation to the form, which is simple to understand
-23+5(7-12x)=7(1-6x)-3(2x+1)

Reorder the terms in parentheses
-23+(+35-60x)=7*(1-6x)-3*(2x+1)

Remove unnecessary parentheses
-23+35-60x=+7+*(+1-6x+)-3+*(+2x+1+)

Reorder the terms in parentheses
-23+35-60x=+(+7-42x)-3*(2x+1)

Remove unnecessary parentheses
-23+35-60x=+7-42x-3+*(+2x+1+)

Reorder the terms in parentheses
-23+35-60x=+7-42x+(-6x-3)

Remove unnecessary parentheses
-23+35-60x=+7-42x-6x-3

We move all terms containing x to the left and all other terms to the right.
-60x+42x+6x=+7-3+23-35

We simplify left and right side of the equation.
-12x=-8

We divide both sides of the equation by -12 to get x.
x=0.66666666666667

See similar equations:

| 5n+2=3n | | 18+n=18 | | x^2+y^2=4x+10y | | 5n+2=3g | | n*2-4n=11 | | 7x-5+3x=14x | | 3x-4+2x(x+1)=7 | | f(x)=275+0.025x | | 6x-12=2x+18 | | 50x-100=600 | | x^2+y^2+2x-8y+26=0 | | n^3+6n^2+9n+4= | | 7v-6=4v+6 | | 4a+29=a+47 | | 4s-97=3s-63 | | an=5n-19 | | xy^2-5xz+4x^2yz^3=0 | | 3v+4=-8 | | x^2+8.544*x-13.5=0 | | x^2+sqrt(73)-13.5=0 | | 9.6s+9.4s=6 | | i^3(5+i)+7i=0 | | 19s=6 | | 7(a-3)=4a+9 | | 4x*8=5x | | (-3i)(3i)-(2+2i)=0 | | 9-0.2= | | 9.75+1.3(x-0.7)=0.12(x+10)+5x | | 9y^2=11 | | -21d=6 | | 10x+5(a-3)=15 | | 3u-83=u+15 |

Equations solver categories